2017
DOI: 10.1051/0004-6361/201629739
|View full text |Cite
|
Sign up to set email alerts
|

Protostellar accretion traced with chemistry

Abstract: Context. Understanding how accretion proceeds is a key question of star formation, with important implications for both the physical and chemical evolution of young stellar objects. In particular, very little is known about the accretion variability in the earliest stages of star formation. Aims. To characterise protostellar accretion histories towards individual sources by utilising sublimation and freeze-out chemistry of CO. Methods. A sample of 24 embedded protostars are observed with the Submillimeter Arra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 80 publications
4
60
1
Order By: Relevance
“…The outward shift of the water snow line in IRAS 15398-3359 is further confirmed by HDO observations (Bjerkeli et al 2016). Similarly, the CO snow line can be used to probe episodic accretion Anderl et al 2016;Frimann et al 2017). The radii of several CO snow lines reported by Jørgensen et al (2015) and Frimann et al (2017) are larger than those predicted from the current luminosities.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…The outward shift of the water snow line in IRAS 15398-3359 is further confirmed by HDO observations (Bjerkeli et al 2016). Similarly, the CO snow line can be used to probe episodic accretion Anderl et al 2016;Frimann et al 2017). The radii of several CO snow lines reported by Jørgensen et al (2015) and Frimann et al (2017) are larger than those predicted from the current luminosities.…”
Section: Introductionmentioning
confidence: 55%
“…Similarly, the CO snow line can be used to probe episodic accretion Anderl et al 2016;Frimann et al 2017). The radii of several CO snow lines reported by Jørgensen et al (2015) and Frimann et al (2017) are larger than those predicted from the current luminosities. They concluded that 20%-50% of their sample sources have experienced recent accretion bursts.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Only a few outbursts have been detected on a deeply embedded Class 0 star (Kóspál et al 2007;Safron et al 2015;Hunter et al 2017), the stage when the star should accrete much of its mass-although many FUor objects retain some envelopes and are classified as Class I objects (e.g., Zhu et al 2008;Caratti o Garatti et al 2011, Caratti O Garatti et al 2016Fischer et al 2012;Green et al 2013;Kóspál et al 2017). Indirect evidence for outbursts includes chemical signatures of past epochs with high luminosity (e.g., Kim et al 2012;Vorobyov et al 2013;Jørgensen et al 2015;Frimann et al 2017) and periodic shocks/bullets along protostellar jets, which may offer a historical record of accretion events (e.g., Reipurth 1989;Raga et al 2002;Plunkett et al 2015). In addition to these large events, instabilities in the inner disk likely lead to more frequent but smaller bursts of accretion, as seen in more evolved disks (e.g., Costigan et al 2014;Venuti et al 2014;Cody et al 2017).…”
Section: Introductionmentioning
confidence: 99%